2015
DOI: 10.1111/cbdd.12577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Kojic Acid Derivatives Containing 1,2,4‐triazole as Potent Tyrosinase Inhibitors

Abstract: A series of 5-substituted-3-[5-hydroxy-4-pyrone-2-yl-methymercapto]-4-amino-1,2,4-triazole derivatives were synthesized by nucleophilic substitution reaction of 5-hydroxy-2-chloromethyl -4H-pyran-4-one with 5-substituted-3-mercapto-4-amino-1,2,4-triazole, and their inhibitory effects on mushroom tyrosinase were evaluated. The results indicated that most of the synthesized compounds exhibited significant inhibitory activity. Specifically, 5-(4-chlorophenyl)-3-[5-hydroxy-4-pyrone-2-yl-methymercapto]-4-amino-1,2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
0
12
0
3
Order By: Relevance
“…Moreover, it has been described that 1,2‐3‐triazole‐containing analogs of the naturally occurring cyclo[Pro‐Val‐Pro‐Tyr] (such as C ) were effective tyrosinase inhibitors (IC 50 = 0.5 m m ) . It has been also reported that the kojic acid derivative containing 1,2,4‐triazole ( D ) exhibited better tyrosinase inhibitor activity (IC 50 = 4.50 μ m ) than kojic acid (IC 50 = 19.00 μ m ) . Considering these structural features and principles of bioisoterism, we designed a series of tyroinase inhibitors by employing fragment‐based drug design strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been described that 1,2‐3‐triazole‐containing analogs of the naturally occurring cyclo[Pro‐Val‐Pro‐Tyr] (such as C ) were effective tyrosinase inhibitors (IC 50 = 0.5 m m ) . It has been also reported that the kojic acid derivative containing 1,2,4‐triazole ( D ) exhibited better tyrosinase inhibitor activity (IC 50 = 4.50 μ m ) than kojic acid (IC 50 = 19.00 μ m ) . Considering these structural features and principles of bioisoterism, we designed a series of tyroinase inhibitors by employing fragment‐based drug design strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Як вихідні речовини обрали 2-бромбензойну кислоту, з якої через низку послідовних стадій отримали 5-(2-бром-феніл)-4-аміно-4Н-1,2,4-тріазол-3-тіон [10][11][12].…”
Section: матеріали і методи дослідженняunclassified
“…Для аналізу солі очищені перекристалізацією із суміші вода:ацетон (1:3). (8,9,11). До 0,01 моль 2-(5-(2-бром-феніл)-4-аміно-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти у 30 мл і-пропанолу додають 0,01 моль піпе-ридину (8), морфоліну (9) або піперазину (11) і нагрі-вають до розчинення.…”
Section: експериментальна частина 2-(5-(2-бромфеніл)-4-аміно-4н-124unclassified
See 1 more Smart Citation
“…This enzyme is widely distributed in plants, microorganisms, fungi, and animals [36]. Tyrosinase is also responsible for the production of neuromelanin.…”
Section: Introductionmentioning
confidence: 99%